Oxidative stress in elite athletes training at moderate altitude and at sea level. Issue 6 (3rd July 2018) - León-López, Josefa; Calderón-Soto, Carmen; Pérez-Sánchez, Matías; Feriche, Belén; Iglesias, Xavier; Chaverri, Diego; Rodríguez, Ferran A.
Abstract : Using a controlled parallel group longitudinal trial design, we investigated the effects of different training interventions on the prooxidant/antioxidant status of elite athletes: living and training at moderate altitude for 3 (Hi-Hi3) and 4 weeks (Hi-Hi), and for 4 weeks too, living high and training high and low (Hi-HiLo) and living and training at sea level (Lo-Lo). From 61 swimmers, 54 completed the study. Nitrites, carbonyls, and lipid peroxidation (LPO) levels were assessed in plasma. Enzymatic antioxidants glutathione peroxidase (GPx) and glutathione reductase (GRd), and non-enzymatic antioxidants total glutathione (GST), reduced glutathione (GSH) and oxidized glutathione (GSSG) were analysed in the erythrocyte fraction. At the end of the intervention, nitrites levels were similar in all altitude groups but higher than in the Lo-Lo controls ( P = .02). Hi-HiLo had greater GPx activity than Hi-Hi and Hi-Hi3 during most of the intervention ( P ≤ .001). GRd activity was higher in Lo-Lo than in Hi-Hi at the end of the training camp ( P ≤ .001). All groups showed increased levels of LPO, except Lo-Lo, and carbonyls at the end of the study ( P ≤ .001). Training at altitude for 3 or 4 weeks drives oxidative stress leading to cellular damage mainly by worsening the antioxidant capacities. The GSSG/GSH ratio appears to be related to perceived exertion and fatigue. The stronger antioxidant defence showed by the Hi-HiLo group suggests an inverse relationship between redox alterations and performance. Further studies are required to investigate the role of oxidative stress in acclimatization, performance, and health.